‘The flowing-haired friend of the fire of altars’ - Clunies Ross, Margaret (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: There are very few sources, other than material remains and spatial arrangements revealed by archaeological excavation, that can give modern researchers access to the thought-world of pre-Christian Scandinavian religion. Some skaldic poetry presumed to have been composed before the Conversion may offer a window onto this thought-world. This article investigates how a single kenning from a stanza composed by the tenth-century Icelander Egill Skallagrímsson conceptualised the relationship between the dominant Viking-Age deity Óðinn and the conduct of religious ritual. RESUME: Der findes meget få kilder, bortset fra materiel kultur og spatiale organiseringer afdækket gennem arkæologiske udgravning, der kan give moderne forskere adgang til førkristen nordisk religions tankeverden. Nogle skjaldedigte, som antages at være komponeret før konverteringen til Kristendom, kan give et indblik i denne tankeverden. Denne artikel undersøger hvordan en enkelt kenning fra en strofe komponeret af islændingen Egill Skallagrímsson i det tiende århundrede konceptualiserer forholdet mellem den dominerende vikingetidsguddom, Óðinn, og udførelsen af religiøse ritualer